The determinants of housing price in Malaysia / Prisca Gambal - Gambal, Prisca (2019)
In the past few years, Malaysia was experience the changes in house price. The significant changes as it distressed the citizen. This research paper is to investigate the determinants of housing price in Malaysia. This study also examines the relationship between the factors that affect house price. There are five macroeconomic variables that researcher chose which are gross domestic product (GDP), inflation rate, unemployment rate, population and lending rate with house price index. This study is consist of 30 years of period which taken from year 1988 until year 2017. For the data analysis, this study is using Eviews9 to regress the data. Those data will analyse the linear multiple regression model to identify the significant relationship between the variables. The variables will be analyse by using the t-test, ftest, and also run the unit root test to ensure the relationship between the variables. The result finding shows that only GDP and lending rate are significant with the house price index. The study intends to examine the unpredictable of rising in the house price where this study will help investor and the government to plan for a better growth in house price.